In Situ Continuous Monitoring of Borehole Displacements Induced by Stimulated Hydrofracture Growth. Issue 4 (22nd February 2021) - Guglielmi, Y.; Cook, P.; Soom, F.; Schoenball, M.; Dobson, P.; Kneafsey, T.
Abstract: We provide direct observations of the three‐dimensional displacements of a fluid‐driven fracture during water injections in a borehole at ∼1.5 km depth in the crystalline rock at the Sanford Underground Research Facility (USA). Micro‐shearing of the borehole initiates on a foliation plane at 61% of the minimum principal stress σ 3 . As the fluid pressure increases further up to 112% of σ 3, borehole axial and radial displacements increase with injection time highlighting the opening and sliding of a new hydrofracture growing ∼10 m away from the borehole, in accordance with the ambient normal stress regime and in alignment with the microseismicity. Our study reveals how important it is to consider monitoring zonal deformation in conjunction with pressure and flow to better manage the complex hydromechanical evolution of the growing fracture. Plain Language Summary: We provide an observation of the direct coupling between three‐dimensional displacement, injection pressure, and flow during growth of a hydraulic fracture in rock types (intact metamorphic rock) relevant for enhanced geothermal systems and the mining industry. The displacement data indicate a complex interplay of fracture opening and fracture dilation including interaction with natural, preexisting fractures, and induced seismicity. Key Points: Hydrofracture (HF) nucleates on a plane of weakness controlled by the rock fabric HF macroscopic propagation is in good accordance with the stress tensor and the alignment of induced seismicity Borehole displacements highly complement pressure data to estimate fracture orientation and growth away from the borehole